A novel local impedance algorithm to guide effective pulmonary vein isolation in atrial fibrillation patients: Preliminary experience across different ablation sites from the CHARISMA pilot study. (9th July 2020) - Segreti, Luca; De Simone, Antonio; Schillaci, Vincenzo; Bongiorni, Maria Grazia; Pelargonio, Gemma; Pandozi, Claudio; Di Cori, Andrea; Stabile, Giuseppe; Pepe, Marco; Zucchelli, Giulio; Shopova, Gergana; De Lucia, Raffaele; et al.
Abstract: Introduction: Recently, a novel technology able to measure local impedance (LI) and tissue characteristics has been made available for clinical use. This analysis explores the relationships among LI and generator impedance (GI) parameters in atrial fibrillation (AF) patients. Characterization of LI among different ablation spots and procedural success were also evaluated. Methods and Results: Consecutive patients undergoing AF ablation from the CHARISMA registry at five Italian centers were included. A novel radiofrequency (RF) ablation catheter with a dedicated algorithm (DIRECTSENSE™) was used to measure LI and to guide ablation. The ablation endpoint was pulmonary vein (PV) isolation. We analyzed 2219 ablation spots created around PVs in 46 patients for AF ablation. The mean baseline tissue impedance was 105.8 ± 14 Ω for LI versus 91.8 ± 10 Ω for GI ( p < .0001). Baseline impedance was homogenous across the PV sites and proved higher in high‐voltage areas than in intermediate‐ and low‐voltage areas and the blood pool ( p < .001). Both LI and GI displayed a significant drop after RF delivery, and absolute LI drop values were significantly larger than GI drop values (14 ± 8 vs. 3.7 ± 5 Ω, p < .0001). Every 5‐point increment in LI drop was associated with successful ablation (odds ratio = 3.05, 95% confidence interval: 2.3–4.1, p < .0001). Conversely, GI drops were not significantly different comparing successful versus unsuccessful sites (3.7 ± 5 vs. 2.8 ± 4 Ω, p = .1099). No steam pops or major complications occurred during or after the procedures. By the end of the procedures, all PVs had been successfully isolated in all patients. Conclusions: The magnitude of the LI drop was more closely associated with effective lesion formation than the GI drop.